Pseudo-boehmite AlOOH supported NGr composite-based air electrode for mechanically rechargeable Zn-air battery applications - Kharabe, Geeta Pandurang; Manna, Narugopal; Nadeema, Ayasha; Singh, Santosh K.; Mehta, Shweta; Nair, Aathira; Joshi, Kavita; Kurungot, Sreekumar (Journal of Materials Chemistry A, 2022)
Both mechanically and electrically rechargeable zinc-air batteries (ZABs) have received much interest due to their high energy density and suitability for mobile and stationary applications. However, their commercialization has been impeded by the lack of robust, low-cost and environmentally benign catalyst materials that can be easily scaled up. In this context, the present work introduces a new type of transition metal-free catalytic material (AlOOH/NGr) by anchoring the pseudo-boehmite phase of aluminium oxyhydroxide (AlOOH) nanosheets over nitrogen-doped graphene (NGr) via a single-step and straightforward hydrothermal process. Furthermore, density functional theory (DFT) based computation demonstrates that the nucleation of AlOOH starts from the N-sites and points towards the strong surface interaction between AlOOH and NGr via doped nitrogen. AlOOH/NGr consisting of thin layered pseudo-boehmite sheets uniformly distributed over NGr has displayed an oxygen reduction reaction onset potential of 0.83 V and a half-wave potential of 0.72 V, along with good catalytic durability in alkaline medium. With this, AlOOH/NGr, when used as an air electrode for fabricating a primary Zn-air battery, the system has exhibited an open circuit voltage of similar to 1.27 V with a flat discharge profile at a current rate of 10 mA cm(-2). The fabricated system delivered a specific capacity of similar to 720 mA h g(-1) and a high power density of 204 mW cm(-2) and is comparable to the counterpart system based on the state-of-the-art Pt/C (20 wt% Pt) cathode. Additionally, the homemade battery was able to maintain its performance after 4 times of mechanical recharging of the battery, which lasted for more than 35 h at a discharge current density of 10 mA cm(-2). Thus, we have uncovered the potential of an earth-abundant metal-based catalytic system for fabricating and demonstrating a robust mechanically rechargeable zinc-air battery.